1997
DOI: 10.1088/0953-4075/30/9/017
|View full text |Cite
|
Sign up to set email alerts
|

The dynamical behaviour of and in a strong, femtosecond, titanium:sapphire laser field

Abstract: Detailed measurements of and dissociation fragment kinetic energy dependences on laser intensity, using 150 fs, 800 nm pulses, are presented. The yields for both molecular and atomic ions are also given. The observed three-peak kinetic energy spectrum carries within it the signature of the different stages of the interaction. The two lower energy peaks are a product of bond softening (and above threshold) dissociation of the molecular ion from Franck - Condon populated vibrational levels. The third higher-en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 26 publications
(35 reference statements)
5
35
0
Order By: Relevance
“…Outside the region where the two pulses overlap the high-energy band is delay-independent. This structure was observed in numerous previous studies 8,9,18,22,[26][27][28][29][30][31][32] and originates from enhanced ionization of the H 2 + molecular ion at internuclear distances R of ~ 4-7 a.u., as was discussed above. Higher proton energies which can be observed in the region of overlapping pulses are due to the higher laser intensity experienced by the molecule: it was demonstrated that with increasing intensity the CREI peak broadens and shifts to higher energies 18,[26][27][28] .…”
Section: Resultssupporting
confidence: 62%
“…Outside the region where the two pulses overlap the high-energy band is delay-independent. This structure was observed in numerous previous studies 8,9,18,22,[26][27][28][29][30][31][32] and originates from enhanced ionization of the H 2 + molecular ion at internuclear distances R of ~ 4-7 a.u., as was discussed above. Higher proton energies which can be observed in the region of overlapping pulses are due to the higher laser intensity experienced by the molecule: it was demonstrated that with increasing intensity the CREI peak broadens and shifts to higher energies 18,[26][27][28] .…”
Section: Resultssupporting
confidence: 62%
“…This band is due to Coulomb explosion, where, similar to the previous case, both ionization steps can either occur within one pulse (most likely the probe one, see Fig. 3a and 3b For very small delays this band is shifted towards larger proton energies due to the higher laser intensities achieved in case of constructive interference between both pulses [20,[36][37][38][39].…”
Section: Resultssupporting
confidence: 54%
“…Whereas the Coulomb explosion peak is more intense than for 3*10 14 W/cm 2 (compare Fig. 3a and 3b), it is still considerably suppressed compared to the case of longer pulses of the same intensity [36][37][38][39][40]. Alternatively, the H 2 + ion, which has been created in the pump pulse and remained bound until the pulse has gone, can be dissociated by the probe pulse: pump: H 2 → H 2 + + e -; probe: H 2 + → H + + H (pathway 1b).…”
Section: Methodsmentioning
confidence: 80%
See 1 more Smart Citation
“…Third, the quite large difference in the ionization energies of H 2 (15.2 eV) and H 2 + (29.9 eV) is the basis of a two-step treatment: Starting with the neutral molecule in a strong laser pulse the first electron will be easily removed creating the ionic state which will subsequently undergo further fragmentation processes. Most experiments have used the neutral molecule as a target (Zavriyev et al 1993, Walsh et al 1997, Thomson et al 1997, Gibson et al 1997, Frasinski et al 1999, Posthumus et al 2000, Rottke et al 2002. However, the formation and fragmentation of H 2 + occurs in the same laser pulse and, thus, cannot be completely disentangled (Walsh et al 1998).…”
Section: Introductionmentioning
confidence: 99%